ANALISIS PERSEPSI PENGUNJUNG DAN MASYARAKAT DALAM PENGEMBANGAN OBJEK WISATA ALAM AIR TERJUN WAY LALAAN - Della Tiara Monik; Sugeng Prayitno Harianto; Agus Setiawan (Lambung Mangkurat University-Indonesia, 2021)
Way Lalaan Waterfall is located in Kota Agung Timur, Tanggamus Regency, Lampung. Way Lalaan Waterfall has a lot of potential that can be developed into a great opportunity in the tourism sector in Tanggamus Regency. The purpose of this analysis is to find out how visitors and community perceptions of the development of Way Lalaan Waterfall Nature Tourism Objects in assessing tourist access and on the condition of the tourist attraction facilities. This observation uses a qualitative descriptive method. Primary data obtained through observation techniques and interviewing 99 visitors and 30 respondents from the respondent community using a questionnaire. In this study the data were analyzed using a likert scale measurement. Measurement of valuation instrument items on a likert scale that includes a range of values ≤ 5 means very good, range of values 4 ≤ 4.5 is good, range 3 ≤ 3.5 is sufficient, range 2 ≤ 2.5 is not good, and range ≥ 1 is not good, tourist accessibility (4,4) and included in the good category, assessment of physical condition (3,8) included in the good category, assessment of hygiene conditions (3,4) included in the adequate category, assessment of the condition of infrastructure (3,6) in the good category and in the rating of tourist satisfaction (4.0) in the good category. The results of the assessment of the average public perception of tourism support at Way Lalaan Waterfall (4.0) fall into either category. This shows that its need to be an increase in the field of cleanliness. Efforts to develop a tourist attraction can be done with a good and structured strategy in order to increase interest in visiting the tourist attraction.